To the last breath : a memoir of going to extremes - Slakey, Francis. (Simon & Schuster, 2012)
A Georgetown University physics professor describes the rigidly scheduled and isolated existence he led before embarking on a life-risking effort to climb the world's highest mountains and surf every ocean.